Risks and Protective Factors Associated With Mental Health Symptoms During COVID-19 Home Confinement in Italian Children and Adolescents: The #Understandingkids Study - Oliva, Salvatore; Russo, Giusy; Gili, Renata; Russo, Luigi; Di Mauro, Antonio; Spagnoli, Alessandra; Alunni Fegatelli, Danilo; Romani, Maria; Costa, Anna; Veraldi, Silvio; Manti, Filippo (Frontiers in Pediatrics, 2021)
Objective To identify risk and protective factors for mental health symptoms associated with lifestyle changes caused by home confinement in pediatric subjects and in children and adolescents with a neuropsychiatric disorder. Study design This was a prospective, cross-sectional study conducted from May 10 to May 31, 2020. Two online anonymous surveys were developed: population-based and clinical-based (children with neuropsychiatric disorders). Outcomes included emotional and behavioral symptoms, as assessed by psychometric scales (BPSC, PPSC, PSC, CES-DC and SCARED, respectively), and lifestyle changes during home confinement (i.e. physical activity, screen time, home schooling, reading). Results The sample included 9688 pediatric subjects, and 289 children and adolescents with a neuropsychiatric disorder. The presence of siblings was a protective factor in all ages. In pre- and school children: male sex, a diagnosis of autism, residency in highly affected areas, high parental educational level or job loss, and screen time (>2hours/day) were risk factors. Physical activity, home-schooling, reading, talking with other people were protective factors. Residency in highly affected areas, a diagnosis of mood disorder, parental job loss, and screen time, were associated with a worsening of the depressive symptoms, whereas physical activity, talking with other people, playing with parents were protective activities. Screen time was also a risk factor for anxiety symptoms, while physical activity, reading and talking with other people were protective factors. Conclusions This study identified risk and protective factors for mental health symptoms associated with lifestyle changes caused by COVID-19 home confinement to promote mental wellbeing in pediatrics during pandemic times.